2015
DOI: 10.1002/2015gc005766
|View full text |Cite
|
Sign up to set email alerts
|

Water input and water release from the subducting Nazca Plate along southern Central Chile (33°S–46°S)

Abstract: The age of the subducting Nazca Plate off Chile increases northward from 0 Ma at the Chile Triple Junction (468S) to 37 Ma at the latitude of Valparaıso (328S). Age-related variations in the thermal state of the subducting plate impact on (a) the water influx to the subduction zone, as well as on (b) the volumes of water that are released under the continental fore arc or, alternatively, carried beyond the arc. Southern Central Chile is an ideal setting to study this effect, because other factors for the subdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 107 publications
(198 reference statements)
3
28
0
Order By: Relevance
“…The Nazca plate in south Chile is younger and hotter, which may lead to basalt‐eclogite dehydration at shallower depths than central Chile. This is supported by numerical modeling by Völker and Stipp () who showed that a significant dehydration event occurs approximately 50 km west of the volcanic arc for the Maule region but occurs further west when the Nazca plate is younger (i.e., in south Chile). This is also supported by earlier numerical work showing that intermediate temperature slabs release more water earlier (i.e., shallower) than low‐temperature slabs (e.g., Kerrick & Connolly, ).…”
Section: Inversion Results and Interpretationsupporting
confidence: 59%
See 1 more Smart Citation
“…The Nazca plate in south Chile is younger and hotter, which may lead to basalt‐eclogite dehydration at shallower depths than central Chile. This is supported by numerical modeling by Völker and Stipp () who showed that a significant dehydration event occurs approximately 50 km west of the volcanic arc for the Maule region but occurs further west when the Nazca plate is younger (i.e., in south Chile). This is also supported by earlier numerical work showing that intermediate temperature slabs release more water earlier (i.e., shallower) than low‐temperature slabs (e.g., Kerrick & Connolly, ).…”
Section: Inversion Results and Interpretationsupporting
confidence: 59%
“…These fluids then lower the solidus temperature of the surrounding mantle rocks, generating hydrous mafic melts. Determining the amount of water, the depth at which it is released, and the zones of accumulation of aqueous fluids and partial melt are critical parameters in examining magma flux and magma genesis (Petrelli et al, ; Völker & Stipp, ). Furthermore, it has been widely suggested that fluids control the distribution of seismic and aseismic zones within a subduction zone and thus understanding seismicity and fluid relationships is important (Saffer, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is, in turn, in agreement with the high-quality reflectivity images along the profile (Groß et al 2008;Micksch 2008). It is also in agreement, as will be discussed in more detail below, with a model for water being transported down and released from the subduction zone (Völker & Stipp 2015).…”
Section: Poisson's Ratio Model V P /V S Ratio Model and Observed Clusupporting
confidence: 70%
“…• W. A study from Völker & Stipp (2015) could explain this observation. They ran thermal models to estimate the amount of water carried into the south-central Chile subduction zone and released by the oceanic crust and mantle for Nazca plate segments of different age.…”
Section: Correlating S-wave Velocity and Poisson's Ratio Models To Otmentioning
confidence: 93%
See 1 more Smart Citation